Analisis Keberlanjutan Usaha Kecil Berbasis Kearifan Lokal (Studi Kasus Rumah Makan Holat Suka Rame Kec. Sungai Kanan, Kab. Labuhan Batu Selatan) - Nasution, Rahman Ali; Syahriza, Rahmi; Naser Daulay, Aqwa (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This study aims to determine and analyze the sustainability of the traditional holat food business based on local wisdom and is the main menu at the Holat Suka Rame restaurant in Sungai Kanan District, Labuhan Batu Selatan Regency. The method used in this research is descriptive with a qualitative approach, the research informants are business owners, children of business owners, employees, and 2 customer informants. Data collection is done through interviews, observation, and documentation, the data is then collected to be analyzed qualitatively descriptive. After collecting, data processing can be concluded that to advance the business, business sustainability must be done systematically. Holat Suka Rame restaurant is one type of local wisdom business that has managed to maintain its success through several strategies applied in mandailing terms called marbagas (hereditary heritage), then in business management they apply the mandailing philosophy of dalihan na tolu (family cooperation), and the Holat Suka Rame restaurant business development strategy to various cities is based on careful calculation, which in mandailing terms is called tamba tupang (strategic planning). by involving all family members in various aspects of the business. By involving all family members in various aspects of operations and maintaining a distinctive taste, this business is able to expand to various cities without competing with each other between branches. The strategic location calculation allows the Holat Suka Rame restaurant to remain crowded during lunch and dinner hours, thus creating prosperity for the extended family that runs it.